Design of Pedal Powered Atta Chakki Based on Engineering Properties of Selected Food Grains - Yallappa D; P F Mathad; Ambrish G; Udaykumar Nidoni; Roopa Bai; Kavan Kumar V; Ravi Y (Archives of Current Research International, 2024)
The study was aimed to determine engineering properties of food grains which play an important role in the design of functional componenets of pedal-operated flour mill. The crops namely rice, pigeon pea, wheat, sorghum, and maize were selected for the study. Pedal operated flour mill comonents were designed and developed based on the variation of the engineering properties viz., size, shape, aspect ratio, volume, geometric mean diameter, sphericity, bulk density, true density, density, porosity, weight of 1000 grains, angle of repose, static coefficient of friction and hardness. These properties were determined and considered for the design of functional components viz., design of hopper, selection of drive mechanism, design of supporting frame, selection of grinding stones, power transmission, processing unit, safety, and ergonomics for easy and effective operation were made. The engineering properties are of great importance towards proper design, efficient process and equipment development. The developed pedal-operated flour mill is suitable for grinding almost all cereals and pulses to produce Rawa, Flour (Atta), and Dhal for human consumption and also for producing poultry/fish feed by grinding agro by-products and wastes.